Structure and mechanism of the tyrosine kinase domain of the insulin receptor - Hubbard, Stevan (Henry Stewart Talks, 2007)
Introduction to receptor tyrosine kinases (RTKs), general mechanisms of protein recruitment to RTKs, Structure of the insulin receptor tyrosine kinase domain (IRK), Autoinhibitory mechanisms in RTKs, Structure of the Src homology-2 (SH2) domain of APS, Structure of the APS SH2 domain bound to IRK, Inhibition of IRK activity by Grb14, Structure of the Grb14 BPS region bound to IRK, Structure of the Grb14 SH2 domain, Model of the interaction between Grb14 and the insulin receptor
Archived at 2018/05/31